Perceptual thresholds for shock-type excitation of the front wheel of a road bicycle at the cyclist's hands - Drouet, J.-M.; Guastavino, C.; Girard, N. (Procedia Engineering, 2016)
Dynamic comfort when riding a road bicycle is closely linked to road vibration transmitted to the cyclist. The perception of vibration transmitted to the cyclist while riding has recently garnered increased research attention. In this study, we present a laboratory set-up to simulate road cycling on a treadmill and use it to assess cyclist's sensitivity to shock-type excitation. We report a perceptual experiment to estimate the perceptual threshold in terms of the absorbed energy at the cyclist's hands when presented with two closely spaced impacts at the front wheel. Ten cyclists took part in a two-alternative forced choice (2-AFC) discrimination task. The results indicate that they were able to discriminate energy differences in the order of 100 mJ.